2018
DOI: 10.1080/13545701.2018.1441534
|View full text |Cite
|
Sign up to set email alerts
|

The Care Economy in Post-Reform China: Feminist Research on Unpaid and Paid Work and Well-Being

Abstract: As China embarked on the path of economic and social reforms, social provisions from the Maoist era were dismantled, and care responsibilities shifted back from the state to the household. Rural-urban migration, a steep decline in fertility, and increasing longevity have led to changes in the age structure of the population both overall and by region. Using seven different surveys, the eleven contributions in this volume study the distributive consequences of post-reform care policies and the impact of unpaid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Between 2010 and 2015, the number of internal migrants grew from 121 million to 247 million, of which 169 million moved from rural to urban areas [10]. This rapid social and economic transition in China may affect the practice of breastfeeding [1113]. A review demonstrated that breastfeeding rates in China fell during the 1970s, especially in big cities, and reached their lowest point in the 1980s.…”
Section: Introductionmentioning
confidence: 99%
“…Between 2010 and 2015, the number of internal migrants grew from 121 million to 247 million, of which 169 million moved from rural to urban areas [10]. This rapid social and economic transition in China may affect the practice of breastfeeding [1113]. A review demonstrated that breastfeeding rates in China fell during the 1970s, especially in big cities, and reached their lowest point in the 1980s.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Margaret Gough (2017) finds that in the US, childbearing strategies such as delaying the first birth that allow women to accumulate human capital yield the largest benefits in terms of labor market outcomes. Moreover, impact evaluation studies suggest that programs and policies to provide reproductive health and childcare services have facilitated increased educational attainment and better labor market outcomes for women, especially tenure, promotion, and retention in formal-sector jobs (Thévenon 2016;Strupat 2017;Connelly et al 2018). A wide variety of actors are engaged in their provision -ranging from state and municipal actors to nongovernmental organizations and community-based groups.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that as the economy system transitions from a planned economy to a market-oriented economy, the problem of family-work conflict increased, particularly for regular female workers. This may due to the decrease of child care support from firms and government (Maurer-Fazio et al 2011;Connelly et al 2018). A child care support policy should be implemented by the Chinese government.…”
Section: Discussionmentioning
confidence: 99%